2021
DOI: 10.1186/s12935-021-01975-z
|View full text |Cite
|
Sign up to set email alerts
|

A seven-gene prognostic signature predicts overall survival of patients with lung adenocarcinoma (LUAD)

Abstract: Background Lung adenocarcinoma (LUAD) is one of the most common types in the world with a high mortality rate. Despite advances in treatment strategies, the overall survival (OS) remains short. Our study aims to establish a reliable prognostic signature closely related to the survival of LUAD patients that can better predict prognosis and possibly help with individual monitoring of LUAD patients. Methods Raw RNA-sequencing data were obtained from F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 51 publications
0
21
1
Order By: Relevance
“…IRGS = β1 × expressionG1 + β2 × expressionG2 + …β n × expressionG n . To validate the predictive performance of the scoring system constructed in this study, we assessed survival differences between subgroups using the Kaplan–Meier survival analysis (log-rank test), and plotted the receiver operating characteristic (ROC) curves compared with previously developed signatures [ 27 30 ]. Furthermore, to validate the predictive performance of the IRGS in the different LUAD subgroups, we also performed a subgroup analysis.…”
Section: Methodsmentioning
confidence: 99%
“…IRGS = β1 × expressionG1 + β2 × expressionG2 + …β n × expressionG n . To validate the predictive performance of the scoring system constructed in this study, we assessed survival differences between subgroups using the Kaplan–Meier survival analysis (log-rank test), and plotted the receiver operating characteristic (ROC) curves compared with previously developed signatures [ 27 30 ]. Furthermore, to validate the predictive performance of the IRGS in the different LUAD subgroups, we also performed a subgroup analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Decreased SUMOylation of Nrf2 and increased ROS stimulate the JNK/c-Jun signaling axis to enhance cell migration and cell adhesion, as well as promote LAC cell invasion [7]. At present, risk score models are utilized to evaluate the prognosis of cancer patients [9][10][11]. Herein, the oxidative stress-related genes (OSRGs) were downloaded from the official website of Gene Set Enrichment Analysis (GSEA).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we explored the differences of the biological pathways and tumor immune microenvironment between high- and low-FRGPI groups. Previously, based on candidate prognostic genes, Li et al (2019) , Al-Dherasi et al (2021) , and Liu et al (2021) identified prognostic signatures in lung adenocarcinoma. These models included 16 genes, 7 genes, and 4 genes, respectively.…”
Section: Discussionmentioning
confidence: 99%